Antioxidant Potential of Endemic Begonia sp. from Flores Island: Phytochemical Analysis and Vocational-Based Phytopharmaceutical Development - Agustina Mogi; Fransiska Gue; Theresia Marsanda Robecka Pilipahi (University of Jember, 2025)
Begonia sp., a tropical species native to Flores Island, is commonly used as a local vegetable; however, its potential as a natural source of antioxidants has not been thoroughly investigated. This study aimed to analyze the phytochemical composition and assess the in vitro antioxidant activity of the ethanol extract. High-performance liquid chromatography (HPLC) analysis revealed a complex profile abundant in phenolic compounds and flavonoids, indicated by a prominent chromatographic peak at 18.529 minutes. The extract exhibited significant antioxidant activity, with an IC50 value of 518.49 µg/mL in the ABTS assay, which is comparable to that of the Trolox standard (IC50 = 495.22 µg/mL). Additionally, the Total Antioxidant Capacity (TAC) was measured at a notably high level of 4,612.63 mg Ascorbic Acid Equivalent per gram of extract (mg AAE/g extract). These significant results provide scientific evidence for the classification of Begonia sp. as a valuable natural source of bioactive compounds, supporting its application in vocational training for the practical development of local phytopharmaceuticals.